2002
DOI: 10.1161/01.res.0000015328.20581.d6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modulation of Interendothelial Gap Junctional Communication by 11,12-Epoxyeicosatrienoic Acid

Abstract: Abstract-Functional gap junctional communication between vascular cells has been implicated in ascending dilatation and the cytochrome P-450 (CYP) inhibitor-sensitive and NO-and prostacyclin-independent dilatation of many vascular beds. Here, we assessed the mechanisms by which the epoxyeicosatrienoic acids (EETs) generated by a CYP 2C enzyme control interendothelial gap junctional communication. In CYP 2C-expressing porcine coronary endothelial cells, bradykinin, which enhances EET formation, elicited a bipha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 43 publications
3
93
0
2
Order By: Relevance
“…We also found that 11,12-EET (1 µM) increased Cx43 in the Triton-soluble fraction, and this increase was inhibited by pretreatment with U0126 ( Figure 10A) and GW1100 ( Figure 10B). There were several Cx43 bands detected indicating various levels of phosphorylation (12,53). These data indicate that 11,12-EET-induced phosphorylation and internalization of Cx43 involves GPR40-activated ERK phosphorylation.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…We also found that 11,12-EET (1 µM) increased Cx43 in the Triton-soluble fraction, and this increase was inhibited by pretreatment with U0126 ( Figure 10A) and GW1100 ( Figure 10B). There were several Cx43 bands detected indicating various levels of phosphorylation (12,53). These data indicate that 11,12-EET-induced phosphorylation and internalization of Cx43 involves GPR40-activated ERK phosphorylation.…”
Section: Resultsmentioning
confidence: 70%
“…Effect of 11,12-EET on Cx43 expression in HUVECs: 11,12-EET alters intercellular gap junction communication by activating Cx43 in ECs (12). Gap junctions are in a constant state of assembly and disassembly (53).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although EETs may not be EDHF, several studies suggest that cytochrome P-450 (CYP450) activity is involved in the mechanism of EDHF-mediated vasodilation (6,22,43,45). For example, sulfaphenazole, an inhibitor of cytochrome 2C isozymes, inhibits EDHFmediated vasorelaxation in the porcine coronary artery (21) and 7-ethoxyresorufin, an inhibitor of CYP450 1A isozyme, inhibits the vasodilation in perfused rat mesenteric (1) and renal (2) vascular beds and the guinea pig cerebral artery (14).…”
mentioning
confidence: 99%